A Phase Ib Study to Evaluate the MEK Inhibitor Cobimetinib in Combination with the ERK1/2 Inhibitor GDC‐0994 in Patients with Advanced Solid Tumors. (28th May 2020) - Weekes, Colin; Lockhart, Albert; LoRusso, Patricia; Murray, Elaine; Park, Erica; Tagen, Mike; Singh, Jatinder; Sarkar, Indrani; Mueller, Lars; Dokainish, Hatem; Shapiro, Geoffrey; Burris, Howard
Abstract: Lessons Learned : Despite strong preclinical rationale, combined cobimetinib‐mediated MEK inhibition and GDC‐0994‐mediated ERK inhibition was not tolerable on two 28‐day dosing schedules in which GDC‐0994 was given for 21 days continuously and cobimetinib administered over 21 days either continuously or intermittently. Adverse events were as expected for mitogen‐activated protein kinase pathway inhibition, but overlapping and cumulative toxicities could not be managed on either dosing schedule. Pharmacokinetic parameters of cobimetinib and GDC‐0994 given in combination were similar to those previously observed in monotherapy studies, so that there was no evidence of drug–drug interaction. Cycle 1 metabolic responses were observed by 18F‐fluorodeoxyglucose‐positron emission tomography but were not predictive of outcome measured by RECIST 1.1. Background: Simultaneous targeting of multiple nodes in the mitogen‐activated protein kinase (MAPK) pathway offers the prospect of enhanced activity in RAS‐RAF ‐mutant tumors. This phase Ib trial evaluated the combination of cobimetinib (MEK inhibitor) and GDC‐0994 (ERK inhibitor) in patients with locally advanced or metastatic solid tumors. Methods: Cobimetinib and GDC‐0994 were administered orally on two separate dosing schedules. Arm A consisted of concurrent cobimetinib and GDC‐0994 once daily for 21 days of a 28‐day cycle; Arm B consisted of intermittent dosing of cobimetinib on a 28‐day cycle concurrent with GDC‐0994 daily for 21 days of a 28‐day cycle. Results: In total, 24 patients were enrolled. For Arm A, owing to cumulative grade 1–2 toxicity, the dose of cobimetinib was decreased. For Arm B, dose increases of GDC‐0994 and cobimetinib were intolerable with grade 3 dose‐limiting toxicities of myocardial infarction and rash. Pharmacokinetic data did not show evidence of a drug–drug interaction. Overall, seven patients had a best overall response of stable disease (SD) and one patient with pancreatic adenocarcinoma had an unconfirmed partial response. Conclusion: The safety profile of MEK and ERK inhibition demonstrated classic MAPK inhibitor–related adverse events (AEs). However, overlapping AEs and cumulative toxicity could not be adequately managed on either dosing schedule, restricting the ability to further develop this combination.